ASSESSMENT OF THE EFFECT OF GRAPHENE OXIDE ON THE FUNCTIONAL AND PHENOTYPICAL PROPERTIES OF BV-2 MICROGLIAL CELLS - СТУПАК, Іван; ОСТАПЧЕНКО, Людмила; ГАРМАНЧУК, Людмила; ГОРБАЧ, Олександр; СЕНЧА-ГЛЕВАЦЬКА, Катерина (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
Background. Determining the effectiveness of therapy for brain pathologies depends on many factors, in particular on glial cells, which are structural and morphofunctional components of the blood-brain barrier and can be involved in a number of pathological conditions of the central nervous system. In the mouse-derived BV-2 cell line, the antigen profile, antimicrobial and phagocytic activity are almost similar to macrophages of the body and therefore they are used as an alternative model system in studies of neurodegenerative diseases. Potential drugs or their carriers at different levels of impact on biological objects are carbon nanomaterials, in particular graphene oxide (GO), which has shown antioxidant activity in the therapy of cardiovascular, neurodegenerative and skeletal muscle diseases. Therefore, the aim of this work is to clarify the role of GO as a potential modifier of polarization of BV-2 microglial cells according to the M2 phenotype.Methods. For the study, OGr obtained from the company "Grafren AB" (Sweden) were used. As a model for determining the phenotypic and morphofunctional features under the influence of OGr, microglial cells of the BV-2 mouse line were used. The assessment of cytotoxic/mitogenic effects was carried out by calculating the ratio of live and dead cells. Determination of lactate dehydrogenase activity (LDH) under the influence of OGr was estimated by the spectrophotometric method according to the rate of NADH oxidation. To determine the content of cells polarized by the M1 and M2 phenotype under the influence of OGr, the method of 3-parameter cytofluorimetry using monoclonal antibodies anti-mouse CD80 FITC, anti-arginase 1 APC, anti-mouse CD80 FITC, anti-mouse iNOS PE was used.Results. When studying the cytotoxic/cytostatic effect of OGr at a concentration of 50 μg/ml, no changes were recorded in the survival and proliferation of BV-2 cells, which was confirmed by the constancy of LDH activity compared to the control, and a 2-fold decrease in the indicator relative to hydrogen peroxide. The results of cytofluorimetric analysis confirmed the increase in the M2 subpopulation (CD80⁺/Arginase-1⁺) of positive BV-2 cells under the influence of graphene oxide compared to the control.Conclusions. The increase in the M2 subpopulation of positive BV-2 cells under the influence of graphene oxide compared to the control indicates its potential antioxidant and immunomodulatory activity.

Вступ. Визначення ефективності терапії патологій головного мозку залежить від багатьох чинників, зокрема від клітин глії, які є структурними та морфофункціональними складниками гематоенцефалічного бар'єра й можуть бути залучені до низки патологічних станів центральної нервової системи. У клітинній лінії мишачого походження BV-2 профіль антигенів, антимікробна та фагоцитарна активність майже аналогічні макрофагам організму, тому їх використовують як альтернативну модельну систему в дослідженнях нейродегенеративних захворювань. Потенційними лікарськими засобами або їхніми носіями на різних рівнях впливу на біологічні об'єкти є вуглецеві наноматеріали, зокрема оксид графену (ОГр), який виявив антиоксидантну активність у терапії серцево-судинних, нейродегенеративних захворювань і хвороб скелетних м'язів. Отже, метою цієї роботи є з'ясування ролі ОГр як потенційного модифікатора поляризації клітин мікроглії лінії BV-2 за фенотипом М2.Методи. Для дослідження були використані ОГр, отримані від компанії "Grafren AB" (Швеція). Як модель для визначення фенотипових і морфофункціональних особливостей за впливу ОГр використано мікрогліальні клітини миші лінії ВV-2. Оцінювання цитотоксичних / мітогенних ефектів проводили при підрахунку співвідношення живих і мертвих клітин. Визначення лактатдегідрогеназної активності (ЛДГ) за впливу ОГр оцінювали спектрофото-метричним методом за швидкістю окиснення NADH. Для визначення вмісту клітин, поляризованих за М1- та М2-фенотипом під впливом ОГр, використовували метод трьохпараметрової цитофлюориметрії із застосуванням моноклональних антитіл антимишиних CD80 FITC, антиаргінази 1 APC, антимишиних CD80 FITC, антимишиних iNOS PE.Результати. При дослідженні цитотоксичного / цитостатичного впливу ОГр у концентрації 50 мкг/мл не зафіксовано змін у виживаності та проліферації клітин BV-2, що підтверджено сталістю ЛДГ-активності порівняно з контролем, і двократним зниженням показника відносно пероксиду водню. За результатами цитофлюориметричного аналізу підтверджено зростання субпопуляції М2 (CD80⁺/Аргіназа-1⁺) позитивних клітин BV-2 під впливом оксиду графену порівняно з контролем.Висновки. Збільшення субпопуляції М2 позитивних клітин BV-2 під впливом оксиду графену порівняно з контролем указують на його потенційну антиоксидантну та імуномодулюючу активність.
ОЦІНКА ВПЛИВУ ОКСИДУ ГРАФЕНУ НА ФУНКЦІОНАЛЬНІ ТА ФЕНОТИПОВІ ВЛАСТИВОСТІ КЛІТИН МІКРОГЛІЇ ЛІНІЇ BV-2
Keywords: Оксид графену (ОГр); клітини мікроглії лінії BV-2; ЛДГ-активність; М1 та М2 поляризовані макрофаги; Оксид графену (ОГр); клітини мікроглії лінії BV-2; ЛДГ-активність; М1 та М2 поляризовані макрофаги